Mechanical properties of UV irradiated bio polymer thin films doped with titanium dioxide - Mohd Rus, Anika Zafiah; Mohid, Siti Rahmah; Sulong, Nurulsaidatulsyida; Din, Abdul Talib; Tuan Ya, Tuan Mohammad Yusoff Shah (Trans Tech Publication, Switzerland, 2013)
This study report on the effect of UV-light on the mechanical properties of bio polymer thin films (BPF) doped with 10% Titanium Dioxide(TiO2). Bio monomer was mixed with 4, 4'-methylenebis (phenylisocyanate) (MDI) to produce neat BPF and TiO2 was added to form BFP doped with 10% TiO2. The film samples were irridiated in UV accelerated Weathermeter at 50 degree C with different exposure time. Universal Testing machine was used to measure the tensil strength and the fracture surfaces of the tensile specimens were observed by scanning Electron Micrisopy (SEM).